Genetic Structure of IQ, Phonemic Decoding Skill, and Academic Achievement - Lazaroo, Nikita K.; Bates, Timothy C.; Hansell, Narelle K.; Wright, Margaret J.; Martin, Nicholas G.; Luciano, Michelle (Frontiers in Genetics, 2019)
The aim of this study was to examine whether phonemic decoding skill (deficits of which characterise dyslexia) shares genetic and/or environmental covariance with scholastic abilities independent of general intelligence. Non-word reading ability, verbal and non-verbal IQ, and standardised academic achievement (Queensland Core Skills Test; QCST) were measured in Australian twins (up to 876 twin pairs and 80 singleton twins). Multivariate genetic analysis showed the presence of a general genetic factor, likely reflecting crystallized ability, which accounted for 45-76% of phenotypic variance in QCST scores, 62% of variance in Verbal IQ, 23% of variance in Performance IQ, and 19% of variance in phonological reading ability. The phonemic decoding genetic factor (explaining 48% of variance in phonemic decoding) was negatively associated with mathematical achievement scores (0.4%). Shared effects of common environment did not explain the relationship between reading ability and academic achievement beyond those also influencing IQ. The unique environmental reading factor (accounting for 26% of variance) influenced academic abilities related to written expression. Future research will need to address whether these reading-specific genetic and unique environment relationships arise from causal effects of reading on scholastic abilities, or whether both are share a common influence, such as pleiotropic genes/environmental factors.